2020
DOI: 10.1136/bmjopen-2019-032057
|View full text |Cite
|
Sign up to set email alerts
|

Improving depression outcomes among Australian primary care patients: protocol for a cluster randomised controlled trial

Abstract: IntroductionDepression is a common and debilitating condition. In Australia, general practitioners (GPs) are the key providers of depression care. However, available evidence suggests that case finding for depression in primary care is poor. This study will examine whether a systematic approach to screening for depression and assessing patient preferences for depression care improves depression outcomes among primary care patients.Methods and analysisA cluster randomised controlled design will be used with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While this may be justifiable and in accordance with guidelines in mild and moderate cases, these data illustrate the paucity of predictors of disease progression and the difficulty of early detection of patients with a developing depression in the primary sector, even in the more severe forms. 24 Surprisingly, even in severe depression, more than half of patients continued their pre-diagnosis antidepressant after being diagnosed with depression in a hospital setting, where shifts to another pharmacological class would most often be clinically reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…While this may be justifiable and in accordance with guidelines in mild and moderate cases, these data illustrate the paucity of predictors of disease progression and the difficulty of early detection of patients with a developing depression in the primary sector, even in the more severe forms. 24 Surprisingly, even in severe depression, more than half of patients continued their pre-diagnosis antidepressant after being diagnosed with depression in a hospital setting, where shifts to another pharmacological class would most often be clinically reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a prior systematic review and meta-analysis can demonstrate the requirement for further clinical trial evidence, and therefore, improve the probability that a further trial will generate impact [ 25 ]. Our prior studies found that RIA is predominantly about the incentives established by the RIAF, and the extent to which they align with the incentives within the prevailing research system [ 74 – 76 , 134 ]. To optimise impact, the principles leverage and align with the incentives in the existing grant application and peer review processes.…”
Section: Discussionmentioning
confidence: 99%
“…General practitioners (GPs) are often the first level of contact in the Australian healthcare system, with mental health related issues representing one of the most common health issues managed by GPs ( Carey et al, 2020 ). However, implementing PGx-guided mental health treatment poses many challenges to primary healthcare providers–these include the limited knowledge and experience of PGx testing, the evidence basis for its use, and the concerns about how it can be incorporated into current workflow ( Vest et al, 2020 ; Jameson et al, 2021 ).…”
Section: Clinical Application Of Pharmacogenetics In Youth Mental Healthmentioning
confidence: 99%